2007
DOI: 10.1074/jbc.m605024200
|View full text |Cite
|
Sign up to set email alerts
|

α-Actinin-4 Is Required for Normal Podocyte Adhesion

Abstract: Mutations in the ␣-actinin-4 gene ACTN4 cause an autosomal dominant human kidney disease. Mice deficient in ␣-actinin-4 develop a recessive phenotype characterized by kidney failure, proteinuria, glomerulosclerosis, and retraction of glomerular podocyte foot processes. However, the mechanism by which ␣-actinin-4 deficiency leads to glomerular disease has not been defined. Here, we examined the effect of ␣-actinin-4 deficiency on the adhesive properties of podocytes in vivo and in a cell culture system. In ␣-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
90
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 90 publications
8
90
0
1
Order By: Relevance
“…We used the following primary antibodies for the experiments: total Ctnnb1 (sc-7199 Santa Cruz Biotechnology); active Ctnnb1 (05-665, Millipore); and ␤-actin (ab8226, Abcam). For Wt1 detection of urinary cells, spot urine was collected and centrifuged, and the sediment was dissolved in loading buffer (32).…”
Section: Methodsmentioning
confidence: 99%
“…We used the following primary antibodies for the experiments: total Ctnnb1 (sc-7199 Santa Cruz Biotechnology); active Ctnnb1 (05-665, Millipore); and ␤-actin (ab8226, Abcam). For Wt1 detection of urinary cells, spot urine was collected and centrifuged, and the sediment was dissolved in loading buffer (32).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a experimental study showed that α actinin-4 null mice have severe glomerular disease, 91 and α actinin-4 is required for normal podocyte adhesion. 92 Little is known about the effects of α actinin-4 on Ang II-related actin cytoskeletal change in podocytes. This work examined the function of α actinin-4 in AT1R signaling and the associated mechanisms leading to FSGS in Neph-hAT1 TGRs.…”
Section: Alpha Actinin-4mentioning
confidence: 99%
“…92 To explore further the mechanisms linking chronically increased AT1R signaling in podocytes and proteinuria, expression levels of α actinin-4 in Neph-hAT1 TGRs (Fig. 4.6.1 a) were determined.…”
Section: Ii-treated Cultured Podocytesmentioning
confidence: 99%
“…[17,24] An in vitro study had proved that podocytes generated from α-actinin-4-deficient mice showed aggregates and increased degradation of the mutant proteins, as well as decreased adhesive ability to GBM components. [25,26] Both in vivo and in vitro studies suggested that the breakdown of cytoskeleton filaments was the final common pathway lead to foot process effacement and aggregated microfilaments of podocytes and its dysfunction. Goode et al [14] reported that the expression of α-actinin-4 in podocytes of MCD was similar to that of normal kidney, while an elevated α-actinin-4 expression could be found in the areas of subepithelial deposits of podocytes in membranous nephropathy.…”
Section: Discussionmentioning
confidence: 99%